Hubungan Gula Darah, Asam Urat dan Hemoglobin dengan Tekanan Darah Lansia: The Relationship between Blood Sugar, Uric Acid, and Hemoglobin with Blood Pressure in the Elderly - Praningsih, Supriliyah; Maryati, Heni; Firranda F, Fitri; Dianita, Eka Mei; Nahariani, Pepin (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Hypertension is a leading cause of death worldwide, with over one billion people suffering from it. Several factors influence blood pressure, including blood sugar, uric acid, and hemoglobin. This study aimed to analyze the relationship between blood sugar, uric acid, and hemoglobin with blood pressure. Methods: The study design was correlational with a cross-sectional approach. The study population was 46 elderly people in Puton Village, Diwek District, Jombang Regency. Data on uric acid, blood sugar, and hemoglobin levels were collected using a multifunction blood test device through peripheral blood sampling. Blood pressure was measured using a sphygmomanometer according to standard guidelines. Data were analyzed using coding, editing, tabulation, and scoring, and statistical tests were performed using the Spearman Rank test. Results: Most respondents (73.9%) had high blood sugar. Most respondents (71.7%) had high uric acid (33%). Half of respondents (50%) had normal hemoglobin (23%). Nearly half of respondents (34%) had prehypertensive systolic blood pressure and stage 1 hypertension (34.8%) each. Half of the respondents had diastolic blood pressure (50%, 23 people) with grade 1 hypertension. The Spearman rank test for blood sugar and uric acid levels on systolic and diastolic blood pressure using SPSS yielded a p value > 0.05, indicating no correlation. The correlation between hemoglobin and diastolic blood pressure yielded a p value > 0.05, indicating no correlation. The hemoglobin-systolic blood pressure test yielded a p value of 0.017, less than 0.05, with a correlation coefficient of 0.349, indicating a moderate correlation between hemoglobin and systolic blood pressure. Conclusion: Proper control of the intervening variables is essential to ensure a truly homogeneous sample of respondents to achieve optimal results. The number of respondents should be increased.